Evaluating the prospect to hedge maize price risk against the Johannesburg Stock Exchange Commodity Derivatives Market prices : The case of Eswatini - Van der Vyver, André (University of Pretoria, 2021)
Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2021.